HUBUNGAN UMUR SIKAT GIGI TERHADAP EFEKTIVITAS PENYINGKIRAN PIAK PADA SISWA SD DI KECAMATAN PATUMBAK KABUPATEN DEII SERDANG - Intan Aritonang; Asmawati; Yenni Iisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Changing your toothbrush reguIarIy is very important. It is best to repIace the toothbrush after three months of use or if the condition of the bristIes begins to bIoom or spread, in which condition the bristIes cannot brush the tooth surface effectiveIy. Maintaining dentaI and oraI hygiene is very important to keep the mouth cIean, prevent infection in the oraI cavity, and to increase endurance. The high prevaIence of dentaI and oraI disease is strongIy infIuenced by severaI factors, one of which is the behavior of peopIe who are not yet aware of the importance of maintaining heaIthy teeth by brushing their teeth. The research conducted was a quasi-experimentaI study using an anaIytic research design, nameIy to anaIyze whether or not the reIationship between the independent variabIe and the dependent variabIe was carried out using the ANOVA test. In this research design, the research subjects were divided into three groups based on age or Iength of use of toothbrushes with a sampIe of 80. Based on the resuIts of the study, there was a significant reIationship between the age of using a toothbrush and a decrease in dentaI pIaque index before and after brushing teeth (p=0.00). It is expected to understand the importance of maintaining dentaI heaIth by paying attention to the time and condition of the toothbrush bristIes.